Dose escalation phase 1 study of radiotherapy in combination with anti-cytotoxic-T-lymphocyte-associated antigen 4 monoclonal antibody ipilimumab in patients with metastatic melanoma. Issue 2 (20th August 2020) - Boutros, Celine; Chaput-Gras, Nathalie; Lanoy, Emilie; Larive, Alicia; Mateus, Christine; Routier, Emilie; Sun, Roger; Tao, Yun Gan; Massard, Christophe; Bahleda, Rastilav; Schwob, Dominique; Ibrahim, Nathalie; et al.
Abstract : Background: A synergy between radiotherapy and anti-cytotoxic-T-lymphocyte-associated antigen 4 (anti-CTLA-4) monoclonal antibody has been demonstrated preclinically. The Mel-Ipi-Rx phase 1 study aimed to determine the maximum tolerated dose (MTD) and safety profile of radiotherapy combined with ipilimumab in patients with metastatic melanoma. Patients and methods: A 3+3 dose escalation design was used with 9, 15, 18 and 24 Gy dose of radiotherapy at week 4 combined with 10 mg/kg ipilimumab every 3 weeks for four doses. Patients with evidence of clinical benefit at week 12 were eligible for maintenance with ipilimumab 10 mg/kg every 12 weeks starting at week 24 until severe toxicity or disease progression. The database lock occurred on April 30, 2019. Tumor growth rate of irradiated lesions and non-irradiated lesions were analyzed to assess the systemic immunologic antitumor response. Blood immune monitoring was performed before and during treatment to determine if radiotherapy could modify ipilimumab pharmacodynamics. Results: 19 patients received ipilimumab between August 2011 and July 2015. Nine patients received the four doses of ipilimumab. All patients received the combined radiotherapy. Grade 3 adverse events occurred in nine patients, the most common being colitis and hepatitis. No drug-related death occurred. Dose limiting toxicity occurred in two of six patients in the cohort receiving 15 Gy. The MTD was 9 Gy. Two patients had complete response, three had partial response response and seven had stable disease, giving an objective response rate of 31% and a clinical benefit rate of 75% at week 24. The median duration of follow-up was 5.8 years (Q1=4.5; Q3=6.8). The median overall survival (95% CI) was estimated at 0.9 years (0.5–2). The median progression-free survival (PFS) (95% CI) was 0.4 (0.2–1.4). Radiotherapy combined with ipilimumab was associated with increased CD4+ and CD8+ICOS+ T cells. Increased CD8+ was significantly associated with PFS. Conclusion: When combined with ipilimumab at 10 mg/kg, the MTD of radiotherapy was 9 Gy. This combination of ipilimumab and radiotherapy appears to be associated with antitumor activity. Increased CD8+ was significantly associated with PFS. Thus, immune biomarkers may be useful for early response evaluation. Trial registration number: NCT01557114 .